Identification and Analysis of Macrozoobenthos in The Reclamation Land Area of Lime Mining - Nurtjahyani, Supiana Dian; Oktafitria, Dwi; Sriwulan, .; Arifin, Ahmad Zaenal; Pambudi, Ahmad Yogi; Purnomo, Eko (Advances in Tropical Biodiversity and Environmental Sciences; Vol 6 No 2 (2022): ATBES, 2022)
Mining activities that occur at PT Semen Indonesia (Persero) Tbk. caused the land to become critical land where the nutrients are low and the ecosystem is disturbed, therefore it is necessary to carry out restoration activities for ex-mining land as an effort to be made for the process of recovering ex-mining land as happened to PT Semen Indonesia Tbk, namely by carrying out reclamation activities. Reclamation is an activity that aims to improve or manage the use of disturbed land due to general mining business activities so that it can function and be efficient in accordance with its designation. This study aimed to analyze the structure of the macrozoobenthos community in the reclamation land ecosystem of PT Semen Indonesia limestone mining. This is expected to provide information on the structure of the ecosystem macrozoobenthos community on reclaimed land. A sampling of macrozoobenthos was carried out in the Sugihan village (SUG) and Mliwang village (MLI), Merakurak district, Tuban regency using the direct hand collecting method. The results of this study indicated that the macrozoobenthos species found on the reclamation land of PT. Semen Indonesia Tbk showed it was included in the medium category.